Crystallization and X-ray diffraction analysis of the N-terminal domain of the Toll-like receptor signalling adaptor protein TRIF/TICAM-1 - Ullah, M. Obayed (International Union of Crystallography, 2013)
As part of the mammalian innate immune response, Toll-like receptors 3 and 4 can signal via the adaptor protein TRIF/TICAM-1 to elicit the production of type-I interferons and cytokines. Recent studies have suggested an auto-inhibitory role for the N-terminal domain (NTD) of TRIF. This domain has no significant sequence similarity to proteins of known structure. In this paper, the crystallization and X-ray diffraction analysis of TRIF-NTD and its selenomethionine-labelled mutant TRIF-NTD(A66M/L113M) are reported. Thin plate-like crystals of native TRIF-NTD obtained using polyethylene glycol 3350 as precipitant diffracted X-rays to 1.9 Å resolution. To facilitate phase determination, two additional methionines were incorporated into the protein at positions chosen based on the occurrence of methionines in TRIF homologues in different species. Crystals of the selenomethionine-labelled protein were obtained under conditions similar to the wild-type protein; these crystals diffracted X-rays to 2.5 Å resolution. The TRIF-NTD and TRIF-NTD(A66M/L113M) crystals have the symmetry of space groups P2(1)2(1)2(1) and P1, and most likely contain two and four molecules in the asymmetric unit, respectively. These results provide a sound foundation for the future structure determination of this novel domain.